The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/jnnp-2020-325994
|View full text |Cite
|
Sign up to set email alerts
|

Early life involvement in C9orf72 repeat expansion carriers

Abstract: ObjectivesThe chromosome 9 open reading frame 72 gene (C9orf72) hexanucleotide repeat expansion (C9orf72RE) is the most common genetic cause of behavioural variant frontotemporal dementia (bvFTD). Since the onset of the C9orf72RE-associated disease is sometimes hard to define, we hypothesise that C9orf72RE may cause a lifelong neuropsychiatric vulnerability. The first aim of our study was to explore lifelong behavioural and personality characteristics in C9orf72RE. Second, we aimed to describe distinctive char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…Interestingly, this was not reflected in participants’ self-reports of psychiatric symptoms, potentially aligning with FTD-typical anosognosia. The present findings converge with those of Gossink et al ,1 underscoring the psychiatric hypervulnerability associated with c9orf72 RE . Our results also add to previously documented empathic deficits2 by revealing increased rates of depressive disorder, post-traumatic stress disorder and substance abuse/dependence, with high comorbidity rates.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, this was not reflected in participants’ self-reports of psychiatric symptoms, potentially aligning with FTD-typical anosognosia. The present findings converge with those of Gossink et al ,1 underscoring the psychiatric hypervulnerability associated with c9orf72 RE . Our results also add to previously documented empathic deficits2 by revealing increased rates of depressive disorder, post-traumatic stress disorder and substance abuse/dependence, with high comorbidity rates.…”
supporting
confidence: 92%
“…Finally, to converge with the findings of Gossink et al ,1 we assessed empathic abilities by means of the Revised Self-Monitoring Scale (RSMS) and the empathic concern scale of the Interpersonal Reactivity Index (IRI), measuring sensitivity to socioemotional cues and allocentric feelings of sympathy for unfortunate others, respectively. Comparisons to healthy reference samples8 9 revealed significantly reduced scores for both variables (RSMS: t(84)=379.21; p<0.001; IRI: t(670)=45.10, p<0.001; see also table 1), replicating other recent findings 2.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…One of the difficulties in defining the prodromal stage in C9orf72 carriers is due to the frequent presence of a prominent psychopathological, rather than cognitive, symptomatology at disease onset. Patients with C9orf72-associated bvFTD often show a constellation of psychiatric symptoms and syndromes [4,[105][106][107], which can be inaugural of the cognitive disorder. Even more noteworthy, a subset of C9orf72 carriers may present with isolated psychiatric phenotypes preceding dementia onset by several years or decades [46].…”
Section: Long-standing Psychopathological and Personality Features In...mentioning
confidence: 99%
“…Many studies have also identified a pattern of variability in the heritability of FTD throughout its clinical subtypes; for instance, a more frequent family history in bvFTD in comparison to non-behavioral variants (primary progressive aphasia and motor phenotypes) ( 117 , 118 ). Furthermore, increasing evidence links the C9ORF72 repeat expansion to a manifestation of atypical psychotic symptoms in carriers before bvFTD ( 70 , 119 , 120 ), including “fixed behavioral patterns in daily life" and limited empathy ( 120 ); conversely, most studies reported no direct, clear statistical correlation between C9ORF72 expression and a primary psychiatric disorder ( 121 ), except for Gosink et al ( 120 ), who described more significant pathological personality traits early in life in positive rather than negative C9ORF72 carriers.…”
Section: Genetic Changes In Ftd and Bdmentioning
confidence: 99%